Multistage strain localisation and fluid-assisted cataclasis in carbonate rocks during the seismic cycle: Insights from the Belluno Thrust (eastern Southern Alps, Italy). (December 2020) - Vignaroli, G.; Viola, G.; Diamanti, R.; Zuccari, C.; Garofalo, P.S.; Bonini, S.; Selli, L.
Abstract: Strain localisation in carbonate rocks impacts upon the nucleation and development of structures within the shallow seismogenic crust. Studying deformed carbonate rocks is thus a key to the refined understanding of the mechanical behaviour of rock successions with high potential to fail coseismically in response to stress accumulation. We studied deformation structures and mechanisms of the Miocene Belluno Thrust from the seismically active eastern Southern Alps, Italy. The thrust contains several structural facies and features (pressure-soluted and veined lithons, cataclasites, S–C fabrics, principal slip surface), which make it possible to define a sequence of deformation events in space and through time during thrusting. Image analysis of cataclasite particle size distribution and morphology, supported by cathodoluminescence imaging, indicates corrosive wearing as the main comminuting mechanism during cataclasis and repeated ingress of overpressured aqueous fluids promoting carbonate clast dissolution. We propose an evolutionary scenario of multiple episodes of fabric formation and rejuvenation that localised and accommodated increasing shear strain into a progressively narrowing fault core. We propose that strain localisation in carbonate rocks can be greatly facilitated by cyclic fluctuations between strain hardening and softening conditions punctuated by transient spikes of coseismic failure accommodated by cataclasis during the ingress of overpressured, chemically reactive fluids that control carbonate precipitation and dissolution. Highlights: The Belluno Thrust provides insights in thrusting mechanics within carbonatic rocks. Thrusting is accommodated by volumetric-to-localised deformation. We describe calcite-precipitating and -dissolving processes during deformation. We provide fractal analysis of the cataclastic textures. Pulses of coseismic rupturing are accommodated by fluid-assisted cataclasis.